Dihydromyricetin-Encapsulated Liposomes Inhibit Exhaustive Exercise-Induced Liver Inflammation by Orchestrating M1/M2 Macrophage Polarization - Zhou, Xi; Yi, Long; Lang, Hedong; Zhang, Jun; Zhang, Qianyong; Yu, Li; Zhu, Jundong; Mi, Mantian (Frontiers in Pharmacology, 2022)
Exhaustive exercise (EE) induced hepatic inflammatory injury has been well reported. Dihydromyricetin (DHM) has shown anti-inflammatory bioactivity and hepatoprotective effects, but is limited by poor bioavailability. Here, high-bioavailability DHM-encapsulated liposomes were synthesized and explored for their therapeutic potential and regulatory mechanisms in a hepatic inflammatory injury model. The animal model was established by swimming-to-exhaustive exercise in C57BL/6 mice, and the anti-inflammatory effects were detected after administration of DHM or DHM liposome. NIR fluorescence imaging was used to assess the potential of liver targeting. The DHM liposome induced macrophage polarization was measured by flow cytometry ex vivo. The anti-inflammatory mechanism of DHM was studied in cell line RAW264.7 in vitro. Liposome encapsulation enhanced DHM bioavailability, and DHM liposome could alleviate liver inflammation more effectively. Moreover, DHM liposome targeted hepatic macrophages and polarized macrophages into an anti-inflammatory phenotype. The SIRT3/HIF-1α signaling pathway could be the major mechanism of DHM motivated macrophage polarization. Our study indicates that DHM liposome can alleviate liver inflammation induced by EE through sustained releasing and hepatic targeting. It's a promising option to achieve the high-bioavailability of DHM. Also, this study provides new insights into the regional immune effect of DHM against inflammation.